Partial Synthetic PPARƳ Derivative Ameliorates Aorta Injury in Experimental Diabetic Rats Mediated by Activation of miR-126-5p Pi3k/AKT/PDK 1/mTOR Expression - Yasmin M. Ahmed; Raha Orfali; Nada S. Abdelwahab; Hossam M. Hassan; Mostafa E. Rateb; Asmaa M. AboulMagd (MDPI AG, 2022)
Type 2 diabetes mellitus (T2D) is a world wild health care issue marked by insulin resistance, a risk factor for the metabolic disorder that exaggerates endothelial dysfunction, increasing the risk of cardiovascular complications. Peroxisome proliferator-activated receptor PPAR) agonists have therapeutically mitigated hyperlipidemia and hyperglycemia in T2D patients. Therefore, we aimed to experimentally investigate the efficacy of newly designed synthetic PPARα/Ƴ partial agonists on a High-Fat Diet (HFD)/streptozotocin (STZ)-induced T2D. Female Wistar rats (200 ± 25 g body weight) were divided into four groups. The experimental groups were fed the HFD for three consecutive weeks before STZ injection (45 mg/kg/i.p) to induce T2D. Standard reference PPARƳ agonist pioglitazone and the partial synthetic PPARƳ (PIO; 20 mg/kg/BW, orally) were administered orally for 2 weeks after 72 h of STZ injection. The aorta tissue was isolated for biological ELISA, qRT-PCR, and Western blotting investigations for vascular inflammatory endothelial mediators endothelin-1 (ET-1), intracellular adhesion molecule 1 (ICAM-1), E-selectin, and anti-inflammatory vasoactive intestinal polypeptide (VIP), as well as microRNA126-5p and p-AKT/p-Pi3k/p-PDK-1/p-mTOR, endothelial Nitric Oxide Synthase (eNOS) immunohistochemical staining all are coupled with and histopathological examination. Our results revealed that HFD/STZ-induced T2D increased fasting blood glucose, ET-1, ICAM-1, E-selectin, and VIP levels, while decreasing the expression of both microRNA126-5p and p-AKT/p-Pi3k/p-PDK-1/p-mTOR phosphorylation. In contrast, the partial synthetic PPARƳ derivative evidenced a vascular alteration significantly more than reference PIO via decreasing (ET-1), ICAM-1, E-selectin, and VIP, along with increased expression of microRNA126-5p and p-AKT/p-Pi3k/p-PDK-1/p-mTOR. In conclusion, the partial synthetic PPARƳ derivative significantly affected HFD/STZ-induced T2D with vascular complications in the rat aorta.